Quality and display life of chilled or frozen all-natural beef and beef-buffalo frankfurters - R. Limsupavanich; Donald H. Kropf; K.A. Hachmeister; T.M. Loughin; Elizabeth A.E. Boyle; Michael A. Boland (Kansas Agricultural Experiment Station Research Reports, 2000)
Chilled (35±3°F) or frozen (0±3°F) all-natural beef and beef-buffalo frankfurters made with or without sodium nitrite (NaNO2) were evaluated. Treatments included frankfurters made with: all-natural beef without NaNO2 and displayed frozen (B0F); all-natural beef and buffalo without NaNO2 and displayed frozen (BU0F); all-natural beef with NaNO2 and displayed frozen (BNF) or chilled (BNC). Batter pH, smokehouse yield, and proximate analysis were determined. No differences (P>.05) were noted in batter pH, smokehouse yield, proximate analysis, or cooking yield. Day of display had no influence (P>.05) on oxidation. However, BU0F had the highest (P.05) during display. Nitrite-free frankfurters can be displayed frozen up to 90 days based on microbial counts, but display life may be limited to 60 days by product color. Inclusion of buffalo did not influence physical or microbiological quality of nitrite-free frozen frankfurters but may accelerate oxidative rancidity.
Keywords: Cattlemen& #x27; s Day; 2000; Kansas Agricultural Experiment Station contribution; no. 00-287-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 850; Beef; All-natural beef-buffalo frankfurters; Nitrite-free; Chilled display; Frozen display